Efficacy and safety of decitabine combined with HAAG (homoharringtonine, aclarubicin, low-dose cytarabine and G-CSF) for newly diagnosed acute myeloid leukemia - Zhu, Jun-Feng; Dai, Hai-Ping; Zhang, Qian-Qian; Yin, Jia; Li, Zheng; Cui, Qin-Ya; Tian, Xiao-Peng; Liu, Si-Ning; Jin, Zheng-Ming; Zhu, Xia-Ming; Wu, De-Pei; Tang, Xiao-Wen (Frontiers in Oncology, 2022)
The 7 + 3 regimen is the front-line induction chemotherapy in patients with newly diagnosed acute myeloid leukemia, with a response rate of 60-80%. But it’s not suitable for all patients especially old/unfit patients because of a higher treatment related toxicity. Therefore, safer and more effective induction therapies are required. In this retrospective study, 50 patients with newly diagnosed acute myeloid leukemia received decitabine combined with HAAG (homoharringtonine, aclarubicin, low-dose cytarabine and G-CSF) as induction chemotherapy. Complete remission (CR) rate was 96% (48/50) and overall response rate was 100%. Of note, All 7 patients harboring FLT3-ITD mutation achieved CR. The median overall survival (OS) was 40.0 months (range 2.0, 58.0). The OS at 1, 3, and 5 years were 75.3%, 54.2%, and 49.3%. The median relapse free survival (RFS) was 38.0 months (range 2.0, 58.0). The RFS at 1, 3, and 5 years were 67.3%, 48.9%, and 45.1%. The OS and RFS of patients who received hematopoietic stem cell transplantation (HSCT) were significantly higher than those who did not undergo HSCT (p=0.017; 0.016). The incidence of grade 3-4 neutropenia and thrombocytopenia was 84% and 88%. Meanwhile, the incidence of grade 3-4 infection and bleeding was only 16% and 6%. There was no early death. In conclusion, DAC+HAAG regimen is effective and well-tolerated as induction therapy in patients with newly diagnosed AML.